Analysis of the Current Situation of Star Chasing and Fan Culture among Middle and High School Students in the Internet + Era - Tang, Xiaoxuan (Transactions on Social Science, Education and Humanities Research, 2024)
Based on the development of the Internet today, teenagers' Internet participation is increasing year by year, and chasing stars has become the main reason why teenagers go online. Learning about the favorite celebrities and following them through social platforms such as Weibo, TikTok, WeChat and Douban has now become a very popular event among teenagers. This article aims to use a questionnaire survey to analyze teenagers’ views on star chasing and their participation in related online and offline star chasing activities, as well as the impact of the entertainment industry fan effect on their allocation of time, energy and money during their growth. After sorting out the data presented in the online questionnaire, 59 females and 11 males participated in the questionnaire, aged between 14-18 years old. In the questionnaire survey, teenagers generally believe that families should guide teenagers correctly in the process of chasing stars, help them establish a correct outlook on life, and chase stars with motivation. In school education, appropriate measures can be taken to guide students to rationally pursue stars, and they must grasp the balance between star chasing and life. In addition, star chasing can also be used as an external motivation for students to learn, and positive guidance should be provided. There is no need to forcibly prohibit it, and do not let it go completely.